Does Elite Competition Inhibit Growth and Delay Maturation in Some Gymnasts? Quite Possibly - Caine, D.; Bass, S. L.; Daly, R. (Pediatric Exercise Science, 2003)
Today, elite young gymnasts undertake training programs of progressive volume and intensity from an early age. For example, talented young female gymnasts often commence training at age 5 or 6 and train more than 20 to 30 hours per week year-round throughout childhood and adolescence. Despite the "normal" short stature of top-level gymnasts and the obvious health benefits of physical activity during growth, there is concern that elite level or those gymnasts involved in heavy training regimens may be at risk for adverse effects on growth and maturation. This concern has been the source of much debate in the literature and is complicated by the difficulties in distinguishing between the genetic predisposition to short stature and late or delayed maturation, and the effect of environmental factors such as nutrition and exercise that may influence growth and maturation. The effect of gymnastics training on growth and maturation is often reported as averaged data: an approach that does not identify individual growth patterns. Finding no difference between groups is not proof that there is "in fact" no difference. Accepting the null hypothesis without the appropriate critical review of both the methodological and statistical power to detect differences is a flawed endeavor. We believe there is compelling "circumstantial" evidence to build a case that preparation for advanced gymnastics competition may place some children and youth at risk of reduced growth and delayed maturation.